Reproductive Biology of Hemibagrus nemurus from the Kampar Kiri River, Mentulik Village, Kampar Kiri Hilir District Kampar Regency, Riau Province - Merissa Handayani; Deni Efizon; Efawani Efawani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTHemibagrus nemurus is present in the Kampar Kiri River. A study aims to understand the reproductive biology aspects of this fish has been conducted from July-August 2019. The fish was sampled 4 times, twice/month. Parameters measured were sexual characteristics, sex ratio, gonad maturity level, gonad somatic index (GSI), fecundity and egg diameter. Results shown that there were 24 males and 28 female (sex ratio 1:1). The female has bigger body than that of the male. Gonad Somatic Index (GSI) of the male was ranged from 0.15%-0.44% andthat of the female was ranged from 0.07% - 4.05%. The fecundity of female was ranged from 2,040 – 26,180 eggs/fish. Egg diameter ranged from 0.33 – 0.44 mm and eggs in different sizes distribute evenly in the ovary, indicating that H. nemurus is a total spawner. Keywords: Catfish, Reproduction, Sex Ratio, GSI, Fecundity, Total Spawner